R-IDEAL: A Framework for Systematic Clinical Evaluation of Technical Innovations in Radiation Oncology - Verkooijen, Helena M.; Kerkmeijer, Linda G. W.; Fuller, Clifton D.; Huddart, Robbert; Faivre-Finn, Corinne; Verheij, Marcel; Mook, Stella; Sahgal, Arjun; Hall, Emma; Schultz, Chris (Frontiers in Oncology, 2017)
The pace of innovation in radiation oncology is high, and the window of opportunity for evaluation narrow. Financial incentives, industry pressure and patients’ demand for high-tech treatments have led to widespread implementation of innovations before, or even without, robust evidence of improved outcomes has been generated. The standard phase I-IV framework for drug evaluation is not the most efficient and desirable framework for assessment of technological innovations. In order to provide a standard assessment methodology for clinical evaluation of innovations in radiotherapy, we adapted the surgical IDEAL framework to fit the radiation oncology setting. Like surgery, clinical evaluation of innovations in radiation oncology is complicated by continuous technical development, team and operator dependence, and differences in quality control. Contrary to surgery, radiotherapy innovations may be used in various ways, eg. at different tumor sites and with different aims, such as radiation volume reduction, and dose escalation. Also, the effect of radiation treatment can be modeled, allowing better prediction of potential benefits and improved patient selection. Key distinctive features of R-IDEAL include the important role of predicate and modeling studies (Stage 0), randomization at an early stage in the development of the technology, and long-term follow up for late toxicity. We implemented R-IDEAL for clinical evaluation of a recent innovation in radiation oncology, the MRI guided linear accelerator (MR-Linac). MR-Linac combines a radiotherapy linear accelerator with a 1.5 Tesla MRI, aiming for improved targeting, dose escalation, and margin reduction, and is expected to increase the use of hypofractionation, improve tumor control,